2020
DOI: 10.1002/admi.202000672
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Transparent Nanowire Architectures with Tunable Geometries for Preventing Marine Fouling

Abstract: Marine biofouling is a sticky global problem that hinders maritime industries. Various microscale surface structures inspired by marine biological species have been explored for their anti‐fouling properties. However, systematic studies of anti‐marine‐fouling performance on surface architectures with characteristic length‐scales spanning from below 100 nm to greater than 10 µm are generally lacking. Herein, a study on the rational design and fabrication of ZnO/Al2O3 core–shell nanowire architectures with tunab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…The wide range of compatible materials (polymers, glass, silicon) and morphological options (holes, pillars) that photonic nanojets enable offer remarkable chances to precisely engineer cell responses. These opportunities can be extended to other living organisms, such as bacteria [ 135 ], algae [ 136 ], and fungi [ 137 ], whose proliferation is of interest for several bio-applications, including the study and treatment of chronic bacterial infections.…”
Section: Nanopatterns For Biomedical Researchmentioning
confidence: 99%
“…The wide range of compatible materials (polymers, glass, silicon) and morphological options (holes, pillars) that photonic nanojets enable offer remarkable chances to precisely engineer cell responses. These opportunities can be extended to other living organisms, such as bacteria [ 135 ], algae [ 136 ], and fungi [ 137 ], whose proliferation is of interest for several bio-applications, including the study and treatment of chronic bacterial infections.…”
Section: Nanopatterns For Biomedical Researchmentioning
confidence: 99%
“…This method can not only be carried out in plane, but also be applied to curved surface. Wang et al [152] found that the application of hydrophilic nanowires on microstructured surfaces can effectively reduce the coverage of marine organisms, which is the reason for the [150] Copyright 2018, Springer-Nature. b) The NW fabrication process is prepared.…”
Section: Textured Structurementioning
confidence: 99%
“…Reproduced with permission. [152] Copyright 2020, Wiley-VCH. g) Magnified images of the nanorods of the prepared structures.…”
Section: Textured Structurementioning
confidence: 99%
See 1 more Smart Citation
“…4 This has led to many biomimicry studies, which attempt to replicate similar nanostructures using engineered materials, both for medical and nonmedical applications, such as marine anti-fouling coatings. 5 Surfaces covered in vertically-aligned nanometre-scale protrusions, such as black silicon, have been shown to exhibit similar antibacterial properties to the cicada wing. [6][7][8] The mechanisms driving this antimicrobial action remain an area of intense discussion in the literature.…”
Section: Introductionmentioning
confidence: 99%